Differential equations of two-phase flow movement in an annular diffuser of the outlet in a hand controlled nozzle of «RAMBOJET» type - Karpenchuk Игорь Васильевич; Parmon Валерий Викторович; Leonik Д.А. (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
The article considers the movement mechanics of liquid, there was received the system of differential equations describing movement mechanics of a two-phase flow in an annular diffuser of the outlet in a hand controlled nozzle of «RAMBOJET» type, which can be used for calculation of geometrical parameters of a nozzle spraying head to receive the necessary dispersion.